Effects of C2-Ceramide and Oltipraz on Hepatocyte Nuclear Factor-1 and Glutathione S-Transferase A1 in Acetaminophen-Mediated Acute Mice Liver Injury - Xin Ma; Xin Ma; Yicong Chang; Yuanyuan Zhang; Ishfaq Muhammad; Chenxi Shi; Rui Li; Rui Li; Changwen Li; Zhi Li; Yuexia Lin; Qing Han; et al. (Frontiers Media S.A., 2018)
In this study, acetaminophen (APAP)-induced acute liver injury mice model was used to investigate the effects of C2-ceramide and oltipraz on hepatocyte nuclear factor 1 (HNF-1) and glutathione S-transferase A1 (GSTA1). Notably, C2-ceramide caused alteration in mice serum transaminases and liver tissue indexes, and aggravated hepatic injury, while oltipraz alleviated hepatic injury. By screening, the optimal concentrations of C2-ceramide and oltipraz were confirmed to be 120 and 150 μmol/L, respectively. In histopathology, karyolysis and more necrotic cells and bleeding spots were appeared on administration of C2-ceramide, but only a small amount of inflammatory cells infiltration was seen after oltipraz treatment. In addition, RT-PCR and western blot results revealed that the mRNA and protein expression levels of HNF-1 and GSTA1 in liver were significantly decreased (p < 0.01) with the administration of 120 μmol/L C2-ceramide. Meanwhile, GSTA1 content in serum increased up to 1.27-fold. In contrast, 150 μmol/L oltipraz incorporation to APAP model mice resulted in obvious elevation (p < 0.01) in the mRNA and protein expression levels of HNF-1 and GSTA1 in liver, and serum GSTA1 content decreased up to 0.77-fold. In conclusion, C2-ceramide could down-regulate the expression of HNF-1 and GSTA1 which exacerbated hepatic injury, while oltipraz could up-regulate the expression of HNF-1 and GSTA1 which mitigated hepatic injury.